Uji Usability Staffing Database Application Based on YII Framework - Mohammad Syahidul Haq; Nur Aini Dwi Setyowati; Najlatun Naqiyah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: The development of information systems and technology plays an important role in improving the quality of management activities, one of which is the management of personnel data. One thing that comes to mind when talking about something that can be used to store, process and provide personnel data is a personal data management system. The personal data management system was developed to make it easy for users to collect and manage their data digitally. The Yii Framework-based Personnel Database application was developed to make it easier for employees and staff of the Faculty of Education, State University of Surabaya to carry out their duties, both teaching and educational staff. Based on the explanation above, this research was conducted to determine the effectiveness of the "Yii Framework-based Personnel Database Application" at the Faculty of Education, State University of Surabaya. This research use a usability measurement test method. Measuring usability means measuring effectiveness, efficiency, and user satisfaction. The results of this study indicate, (1) the calculation results from the usefulness aspect show a percentage of 87, 4%; (2) the calculation results from the second aspect, namely ease of use, showed a percentage of 84, 2%; (3) the calculation result from the third aspect, namely satisfaction, shows a percentage of 85, 3%; (4) the results of the calculation of the overall usability test aspect get a percentage of 85, 4%, this means that the Staffing Database Application Based on Yii Framework, Faculty of Education, Unesa is very effective in supporting employee performance to improve the quality of their work.Keywords: human resource management; web based application; yii frameworkAbstrak: Perkembangan sistem dan teknologi informasi berperan penting dalam peningkatan kualitas kegiatan pengelolaan, salah satunya pengelolaan data kepegawaian. Satu hal yang terlintas dalam pikiran ketika berbicara tentang sesuatu yang dapat digunakan untuk menyimpan, memproses, dan menyediakan data kepegawaian adalah sistem manajemen data pribadi. Sistem pengelolaan data pribadi dikembangkan dengan tujuan untuk dapat memberikan kemudahan bagi penggunanya dalam mengumpulkan dan mengelola datanya secara digital. Aplikasi Database Kepegawaian berbasis Yii Framework dikembangkan dengan tujuan untuk memudahkan pegawai dan staf Fakultas Ilmu Pendidikan Universitas Negeri Surabaya dalam menjalankan tugasnya, baik, staf pendidik maupun kependidikan. Berdasarkan paparan diatas, penelitian ini dilakukan bertujuan untuk mengetahui keefektifan dari “Aplikasi Database Kepegawaian berbasis Yii Framework” di Fakultas Ilmu Pendidikan Universitas Negeri Surabaya. Penelitian ini menggunakan metode uji pengukuran usability. Mengukur usability berarti mengukur efektivitas, efisiensi, dan kepuasaan user. Hasil penelitian ini menunjukkan, (1) hasil perhitungan dari aspek usefulness menunjukkan presentasi sebanyak 87, 4%; (2) hasil perhitungan dari aspek yang kedua yaitu ease of use menunjukkan presentasi sebanyak 84, 2%; (3) hasil perhitungan dari aspek yang ketiga yaitu satisfaction menunjukkan presentasi sebanyak 85, 3%; (4) dari hasil perhitungan keseluruhan aspek uji usability mendapatkan presentasi sebanyak 85, 4%, ini berarti bahwa Aplikasi Database Kepegawaian berbasis Yii Framework Fakultas Ilmu Pendidikan Unesa sangatlah efektif dalam menunjang kinerja pegawai untuk meningkatkan kualitas kerjanya.Kata kunci: manajemen sumber daya manusia; aplikasi berbasis web; yii framework